A Comparative Evaluation of Antibacterial Efficacy of Moringa oleifera Leaf Extract, Octenidine Dihydrochloride, and Sodium Hypochlorite as Intracanal Irrigants against Enterococcus faecalis: An In Vitro Study - Afrah M. Alharbi; Tahani M. Alharbi; Mashael S. Alqahtani; Fathy M. Elfasakhany; Ibtesam K. Afifi; Mona T. Rajeh; Mohamed Fattouh; Laila Mohamed Mohamed Kenawi (International Journal of Dentistry)
Objectives. The aim of this study is to investigate and compare the microbial efficacy of Moringa oleifera leaf extract, octenidine dihydrochloride (OCT), NaOCl, and their combinations as intracanal irrigants against Enterococcus faecalis. Materials and Methods. Sixty single-rooted mandibular premolars were decoronated followed by root canal preparation. Each root specimen was autoclaved, inoculated with E. faecalis, and incubated at 37°C for 48 hr. Then, the specimens were divided into six groups based on the irrigation solution used: 2.5% NaOCl (Group 1), 0.1% OCT (Group 2), M. oleifera leaves extract (Group 3), a combination of M. oleifera extract and 1.25% NaOCl (Group 4), a combination of M. oleifera extract and OCT (Group 5) and normal saline (Group 6). Microbial samples were taken from each root canal before (S1) and after (S2) irrigation and the bacterial viability was assessed using colony-forming units (CFU) on bile esculin agar plates. Results. Comparing the number of CFU/ml before and after irrigation showed a significant reduction (P<0.001) in all studied groups. Comparison between the CFU/ml after irrigation by NaOCl and each of the combination groups showed a significant difference. Conclusion. M. oleifera leaves extract and 0.1% OCT solutions have antibacterial effect against E. faecalis comparable to 2.5% NaOCl and might be used as root canal irrigants. The combination groups showed better antimicrobial activities than individual irrigants. However, further studies are required to investigate the biocompatibility and possible toxic effects of the tested irrigants.